Insuficiente Normatividad Para Tipificar A La Publicidad Engañosa En Los Delitos Contra La Propiedad En Lo Referente A La Estafa Y Otras Defraudaciones” - Jara Suing, Víctor Hugo (2016)
This thesis is developed in the legal field specifically in the lack of regulations to establish a criminal misleading advertising; Since the sanction which gives the consumer organic law is very benevolent in relation to sanctions established for misleading advertising within the framework of the Ecuadorian legislation. The guarantees which the Constitution gives groups of priority attention in what has to do with people, users and consumers constitute or are rights which guarantees to each of the Ecuadorian and Ecuadorians when we went to buy or subscribe to a service, is a right that assists us as consumers; for this reason, the present work is aimed to the lack of efficiency of the existing standard. In this sense, the evolution of advertising, considered to be the most effective means by which have manufacturers and traders of goods or services to find their products and activities to one sufficient number of potential customers and users, and the growing need for protection in an increasingly complex society, they have been setting a figure of particular relevance to the economygiving birth to new forms of crime. The present work which general objective is to carry out a legal analysis of misleading advertising in our country and the lack of characterization as a crime against property in the Ecuadorian criminal legislation, has been tested since by gathering information, field research which made thirty professionals from the right of the judicial district of Loja has been results regarding the issue raisedcoming to the main conclusion that in the legal social reality of our country, by misleading advertising cases are very common in our society, since suppliers covered in a very godly law take advantage and scoff at the consumer to use a hoax with will knowing the economic damage they cause to Ecuadorian households, is becoming a new form of crime; which leads me to recommend that it is urgent, imperative to criminalize misleading advertising within the property crimes in relation to the scam and other fraud, to thus comply with a principle of the State; This illegal conduct should be defined since misleading advertising uses the subjective element dolo therefore.